Transforming the Lives of Mountain Women Through the Himalayan Nettle Value Chain: A Case Study From Darchula, Far West Nepal - Lipy Adhikari; Anu Joshi Shrestha; Tashi Dorji; Eileen Lemke; Bijay Raj Subedee (Mountain Research and Development, 2018)
Naugad is a remote rural municipality in the mountains of far west Nepal with poor accessibility and limited economic opportunities, especially for women and marginalized communities. Promotion of the natural resource-based value chain for allo (the Himalayan nettle, Girardinia diversifolia) was identified as an innovative livelihood strategy by the local community. Value chain development started in 2014. The project was designed to focus on women and include participation by the private sector. This paper analyzes the impact of the project, especially on women's lives, using primary and secondary data. A community-owned enterprise was established with private-sector support from the South Asian Association of Regional Cooperation's Business Association of Home Based Workers (SABAH) Nepal. The enterprise now has 82 members (69 of them women), with 150 households benefiting directly and indirectly. SABAH Nepal provided training in sustainable harvesting and processing techniques and promotes the products in high-end international markets. A buyback guarantee scheme provides security to local artisans. The quality and range of allo products have increased markedly, as has the share in benefits for local people. Skills training and visits to trade fairs have helped women build their capacity and take a leading role in the value chain process. The community-owned enterprise members have earned up to NPR 4000 per month from sewing, more than the local rate for day labor and sufficient to cover general household expenses. More than 25 women entrepreneurs have started microbusinesses related to allo. Allo has become an important economic asset, transforming the lives of mountain women in this village area. The approach has potential for scaling up across the subtropical to temperate areas of the Himalayan region in Bhutan, China, India, Myanmar, and Nepal.